2017
DOI: 10.1111/bph.13713
|View full text |Cite
|
Sign up to set email alerts
|

Chronic drug‐induced effects on contractile motion properties and cardiac biomarkers in human induced pluripotent stem cell‐derived cardiomyocytes

Abstract: BACKGROUND AND PURPOSEIn the pharmaceutical industry risk assessments of chronic cardiac safety liabilities are mostly performed during late stages of preclinical drug development using in vivo animal models. Here, we explored the potential of human induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) to detect chronic cardiac risks such as drug-induced cardiomyocyte toxicity. EXPERIMENTAL APPROACHVideo microscopy-based motion field imaging was applied to evaluate the chronic effect (over 72 h) of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 51 publications
(49 reference statements)
2
36
0
Order By: Relevance
“…These features mean that the contraction property and the conduction property can be simultaneously measured in the same cells at a moderate to high through-put, which supports the potential that MFI has to allow us to use hiPS-CMs in an integrated cardiac safety assessment. Recent studies demonstrated that the cardiac proarrhythmic potential, alterations in contractility, and chronic cardiotoxicity can be evaluated by analyzing the contractile motion obtained by MFI (Kopljar et al, 2017;Hayakawa et al, 2014). However, the conduction property remains to be characterized and used to evaluate cardiac toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…These features mean that the contraction property and the conduction property can be simultaneously measured in the same cells at a moderate to high through-put, which supports the potential that MFI has to allow us to use hiPS-CMs in an integrated cardiac safety assessment. Recent studies demonstrated that the cardiac proarrhythmic potential, alterations in contractility, and chronic cardiotoxicity can be evaluated by analyzing the contractile motion obtained by MFI (Kopljar et al, 2017;Hayakawa et al, 2014). However, the conduction property remains to be characterized and used to evaluate cardiac toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…iPSC-CMs have been used to show decreased contractility, contraction velocity, and beating rates in response to DOX. They have also been used to document stress release biomarkers such as N-terminal pro-brain natriuretic peptide (NT-proBNP), cTnI, and heart-type fatty acid binding protein (hFABP), 75 as well as to identify novel biomarkers such as growth differentiation factor 15 (GDF15). 76 Tissue engineering technologies are also taking the platform beyond the traditional two-dimensional monolayer culture methods towards more physiologic three-dimensional (3D) approaches, allowing the integration of other cardiac cell types into the model.…”
Section: Modelling Anthracycline-induced Cardiotoxicitymentioning
confidence: 99%
“…Hsu et al 75 used four independent hiPSC-CM lines to examine the mechanism of increased DIC in the presence of lapatinib. Other studies have used single hiPSC-CM lines to characterize CAEs caused by doxorubicin, 58,[76][77][78][79][80][81][82][83][84] trastuzumab, 58,85,86 etoposide, 87 arsenic trioxide, 84,88,89 TKIs, [90][91][92][93][94][95][96] and histone deacetylase inhibitors. 84,97,98…”
Section: Hipscs In Pharmacogenomics Researchmentioning
confidence: 99%
“…The concentration of troponin in cell culture media following chemotherapeutic exposure can also be quantified as a surrogate for CM damage. 84,92 This again relies on membrane permeabilization and thus is a measure of late-stage cell damage caused by either apoptosis or necrosis.…”
Section: Defining An Adverse Effect Phenotype In Vitromentioning
confidence: 99%